Navigating Work-Life Balance: Insights from Nepali Students Working in Austria's Gastronomy and Hospitality Sector - Vaidya, Nirsula; Bhandari, Ram (Nepalese Journal of Hospitality and Tourism Management, 2025)
The paper deals with the work-life balance among the Nepali students working in Austria’s gastronomy and hospitality sector. The paper has adopted the case study analysis to navigate the work-life balance scenario of the Nepali students residing in Austria. The paper presents a total of five case studies. An interview was conducted with the selected interviewees to develop case studies. The paper found that participants faced long working hours, cultural adaptations, and language challenges, impacting academic performance and personal lives. Despite these, they demonstrate resilience, acquiring essential skills like financial management. The main concern among the interviewees was a language barrier and difficulty in the adoption of technology within the hospitality sector of Austria.